Mutation Types of CYP71P1 Cause Different Phenotypes of Mosaic Spot Lesion and Premature Leaf Senescence in Rice - Zheng, Yuhan; Xu, Jiangmin; Wang, Fujun; Tang, Yongchao; Wei, Zheng; Ji, Zhiyuan; Wang, Chunlian; Zhao, Kaijun (Frontiers in Plant Science, 2021)
Lesion mimic mutants (LMMs) are ideal materials for studying programmed cell death and defense response in plants. Here we report investigations on two LMMs (msl-1 and msl-2) from the indica rice cultivar JG30 treated by ethyl methyl sulfone. Both of the mutants showed similar mosaic spot lesions at seedling stage, but they displayed different phenotypes along with development of the plants. At tillering stage, larger orange spots appeared on leaves of msl-2, while only small reddish-brown spots exhibit on leaves of msl-1. At heading stage, the msl-2 plants were completely dead, while the msl-1 plants were still alive even if showed apparent premature senility. For both the mutants, the mosaic spot lesion formation was induced by light; DAB and trypan blue staining showed a large amount of hydrogen peroxide accumulated at the lesion sites, accompanied by a large number of cell death. Consequently, reactive oxygen species were enriched in leaves of the mutants; SOD and CAT activities in the scavenging enzyme system were decreased compared with the wild type. In addition, degraded chloroplasts, decreased photosynthetic pigment content, down-regulated expression of genes associated with chloroplast synthesis/photosynthesis and up-regulated expression of genes related to senescence were detected in the mutants, but the abnormality of msl-2 was more serious than that of msl-1 in general. Genetic analysis and map-based cloning revealed that the lesion mimic and premature senescence traits of both the mutants were controlled by recessive mutated alleles of the SL (Sekiguchi lesion) gene, which encodes the CYP71P1 protein belonging to cytochrome P450 monooxygenase family. The difference of mutation sites and mutation types (SNP-caused single amino acid change and SNP-caused early termination of translation) led to the different phenotypes in severity between msl-1 and msl-2. Taken together, this work revealed that the CYP71P1 is involved in regulation of both premature senescence and cell death in rice, and its different mutation sites and mutation types could cause different phenotypes in terms of severity.